Misturas, adjuvantes, dureza e pH da água interferem na aplicação de herbicidas mimetizadores da auxina - Avila Neto, Roberto Costa (2021)
With the launching of Enlist® and Xtend® technologies and, consequently, the increased use of the herbicides 2,4-D and dicamba, new information about the technology of the application of these compounds must be generated, in order to guarantee a correct, safe and efficient. Therefore, the objective of this work was to study the role of the mixture between herbicides and pesticides of different classes in the physico-chemical compatibility of the spray and droplet spectrum; the use of adjuvants in efficiency, chemical aspects and droplet spectrum; and hardness and pH in the control of broadleaved weeds, in aspects of the application technology of auxin-mimicking herbicides. Three works were carried out between the years 2018 and 2020 in field and greenhouse. Overall, we observed the susceptibility of the herbicides 2,4-D and dicamba to pH change, either by mixing with other pesticides, adjuvants or initial pH of the water. In addition, the physical-chemical characteristics and droplet spectrum of these herbicides can be changed depending on the mixture performed. Also, in the production system with crops resistant to auxin-mimicking herbicides, the use of adjuvants, the pH value of the water and the time of preparation of the syrup are determining factors for the success of chemical control strategies, and priority should be given to time of application together with the proper preparation of the syrup and correct use of adjuvants. Based on this, it is evident the need to know the impact of the mixture of 2,4-D and dicamba with different classes of pesticides and the use of adjuvants in the spray, in addition to the role of water quality in the use of these herbicides, since these factors affect the quality and efficiency of the application.